Ketogenic therapies for glioblastoma: Understanding the limitations in transitioning from mice to patients - Clontz, Angela D. (Frontiers in Nutrition, 2023)
Glioblastoma Multiforme is an aggressive brain cancer affecting children and adults frequently resulting in a short life expectancy. Current cancer therapies include surgery and radiation followed by chemotherapy, which due to their ineffectiveness, requires repeated exposure to the same therapies. Since the 1990s, researchers and doctors have explored other therapies, such as diet therapies, to aid in combating gliomas. The ketogenic diet has gained popularity due to Otto Warburg’s theory that tumor cells prefer “aerobic glycolysis” and cannot metabolize ketones. The inability of gliomas to use ketones provides an excellent opportunity to weaken the tumor while protecting healthy cells during cancer treatments. This review will examine some of the current research using the ketogenic diet as a form of cancer therapy to determine if this intervention is manageable and effective in patients with glioblastoma. Peer-reviewed articles from 2009-2019 were used. The primary objective is to distinguish differences between pre-clinical and clinical research to determine if the ketogenic diet is reproducible from mouse models into humans to determine its effectiveness. The analysis revealed several limitations of the ketogenic diet as an intervention. The effectiveness is more robust in mice than in human studies. Furthermore, tolerability is marginally supported in human studies requiring more reproducible research to validate that the intervention is manageable and effective in patients with glioblastoma.